New preparations of diazo compounds and studies of their metal catalysed diverted insertion reactions - Nicolle, Simon (2016)
This Thesis reports some advances in the preparation and metal catalysed reactions of diazo compounds. After an introduction presenting the synthesis routes and the main transformations of this class of compound (Chapter I), the focus is placed on the dehydrogenation of unsubstituted hydrazones as a route to diazo compounds. A review of the reagents previously used for this transformation is followed by the description of the development of the use of potassium N-iodo p-toluenesulfonamide (iodamine-T) as a new reagent for this reaction and its application to a number of hydrazones (Chapter II). After presenting the advantages offered by the handling of diazo compounds in a flow environment, the preparation of a N-iodosulfonamide functionalised resin and its application to the generation of diazocarbonyl compounds in flow are described (Chapter III). A number of examples for the further reaction of diazo compounds generated by this protocol in various in-line reactions (O-H and N-H insertion, cyclopropanation and C H insertion) are described. In particular, the synthesis of spiro-β-lactones by C-H insertion and their further conversion to oxetanes are presented. Moving away from the preparation of diazocarbonyl compounds towards their metal catalysed insertion reactions, the recently described concept of diverted insertion reaction of metallocarbenes into X-H bonds (X = O, N) is first presented and the features of this process are reviewed in light of recent examples (Chapter IV). Following its fortuitous discovery, the diverted insertion reaction of metallocarbenes derived from diazocarbonyl compounds into β-hydroxyketones to give highly functionalised and stereodefined tetrahydrofurans is described (Chapter V). Based on this process, efforts towards the synthesis of naturally occurring hyperlactone C and related compounds are discussed in the same Section. Finally, the application of a diverted insertion strategy to the preparation of functionalised and stereodefined pyrrolidines products from diazocarbonyl compounds and various β aminoketone derivatives is described (Chapter VI).